2022
DOI: 10.1097/icl.0000000000000887
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Clinical Outcomes of Mix-and-Match Implantation of an Extended Depth-of-Focus and a Diffractive Bifocal Intraocular Lens

Abstract: Objectives: To evaluate and compare the clinical outcomes of the extended depth-of-focus intraocular lens (EDOF-IOL) and the diffractive bifocal IOL. Methods: Fifty-six eyes of 28 patients underwent cataract surgery with implantation of an EDOF-IOL (TECNIS Symfony, ZXR00) in their dominant eye and a diffractive bifocal IOL (+3.25 D add TECNIS ZLB00) in their nondominant eye. Monocular and binocular uncorrected distance, intermediate and near visual acuity, defocus curves, contrast sensitivity, patient satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…According to previous studies, UDVA and CDVA were similar between EDOF and monofocal IOL. 27,28 Earlier studies have reported monocular UDVAs of 0.1360.13, 29 0.0160.09, 30 and 0.0260.04 31 for Symfony and 0.1260.14, 28 0.0060.08, 32 , and 20.0160.07 33 Vivity. Earlier studies have reported monocular CDVAs of 20.0560.06, 30 0.0160.03, 34 and 0.0560.08 29 for Symfony and 0.0160.05, 28 20.0260.06, 32 and 20.0160.06 33 for Vivity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to previous studies, UDVA and CDVA were similar between EDOF and monofocal IOL. 27,28 Earlier studies have reported monocular UDVAs of 0.1360.13, 29 0.0160.09, 30 and 0.0260.04 31 for Symfony and 0.1260.14, 28 0.0060.08, 32 , and 20.0160.07 33 Vivity. Earlier studies have reported monocular CDVAs of 20.0560.06, 30 0.0160.03, 34 and 0.0560.08 29 for Symfony and 0.0160.05, 28 20.0260.06, 32 and 20.0160.06 33 for Vivity.…”
Section: Discussionmentioning
confidence: 96%
“…19 Compared with diffractive trifocal IOLs, EDOF IOLs have low incidence rates of postoperative visual symptoms such as photic phenomena. 31 Another study indicated that Symfony IOL implantation was associated with a lower incidence of postoperative visual disturbance and a lower level of subjective perception than trifocal IOL. 25 There was no distinction between the two groups in any of the optical quality parameters (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This extended focal plane can be achieved through the modi cation of spherical aberrations, diffractive optical designs, pinhole effect, or bio-analogical Technologies [11]. Nowadays, to achieve better visual performance, one or more of the available IOL technologies in the market can be combined [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this trend, the ratio of multifocal (bifocal or trifocal), or extended depth-of-focus (EDOF) IOL implantations is increasing [4]. Different bifocal IOL platforms were implanted in the past, but currently, the most common presbyopia correcting IOLs implanted, include on the one hand the trifocal models, like the PanOptix (Alcon Laboratories Inc., Fort Worth, TX, USA), Fine-Vision Micro F IOL (PhysIOL, Liège, Belgium), Acriva Reviol Tri-ED 611 (VSY Biotechnology, Amsterdam, The Netherlands), and AT Lisa tri (Carl Zeiss Meditec AG, Jena, Germany), and on the other hand, modern EDOF like the Symfony (Johnson & Johnson Vision Inc., Santa Ana, CA, USA), or Vivity (Alcon Laboratories Inc., Fort Worth, TX, USA) IOLs [4,5].…”
Section: Introductionmentioning
confidence: 99%